Consequences of Chirality in Directing the Pathway of Cholesteric Helix Inversion of π‐Conjugated Polymers by Light. Issue 2 (3rd December 2020) - Kulkarni, Chidambar; Curvers, Rick H. N.; Vantomme, Ghislaine; Broer, Dirk J.; Palmans, Anja R. A.; Meskers, Stefan C. J.; Meijer, E. W.
Abstract: Control over main‐chain motion of chiral π‐conjugated polymers can lead to unexpected new functionalities. Here, it is shown that by combining photoswitchable azobenzene units in conjugation with chiral fluorene comonomers and appropriate plasticizers, the polymer organization and chiroptical properties of these alternating copolymers steered by light and its state of polarization can be dynamically controlled. The configuration of the stereogenic centers in the side chains of the fluorene units determines the handedness of the cholesteric organization in thermally annealed films, indicating cooperative behavior. The polymer alignment and helicity of the supramolecular arrangement can be switched by irradiating with linearly and circularly polarized light, respectively. Intriguingly, when switching the handedness of thermally induced cholesteric organizations by illuminating with circularly polarized light that is opposite to the handedness of the cholesteric phases, a nematic‐like intermediate state is observed during helix interconversion. By the sequence of irradiation with left and right circularly polarized light followed by thermal annealing, an asymmetric motion, reminiscent of that seen in molecular motors is observed. These findings suggest that functional conjugated polymers can exhibit emergent properties at mesoscopic scale. Abstract : Alternating copolymers of fluorene and azobenzene exhibit exceptional chiroptical properties in annealed thin films. The chiroptical properties, polymer chain alignment, and their supramolecular helicity can be fully controlled by irradiating with polarized light. Intriguingly, the diastereomeric relationship between the supramolecular helicity of polymer and the circular polarization of light leads to an asymmetric helix inversion pathway, reminiscent of molecular motors.